The economics of blockchain and cryptocurrency : a transaction costs revolution - Caton, James Lee (Edward Elgar Publishing, 2022)
"This timely book is an innovative look at how blockchain technology will transform the structure of social and economic life. The security of blockchain supports the provision and maintenance of reliable databases and the creation of rule-based governance protocols. Leading contributors expertly review the impact of blockchain on existing structures of law, monetary systems, supply chains and business organizations. Using economic and institutional theory, the book presents a vision for understanding the future development of blockchain technology and outlines the likely path of transformation that blockchain will drive in industry, supply chains and firms. Furthermore, it answers key questions such as: will Bitcoin or another cryptocurrency become the money of the future? How has blockchain already begun transforming economic activity? How can we evaluate the likely trajectory of technological development and application? This informative book is an excellent resource for academics or professionals interested in a theoretically sound perspective on blockchain. Written in an accessible prose, it provides an introduction for non-experts looking to learn more about the wide-ranging implications of blockchain and cryptocurrency"--